La familia y su incidencia en la inclusión del adulto mayor de la Parroquia El Arenal, Cantón Puyango en la actualidad - Ramón Sánchez, Jaritza Ximena (2025)
This research addresses the role of the family in the inclusion of the elderly in El Arenal Parish, Puyango Canton, highlighting its importance as a support network in the social welfare of this age group. In this context, the growing longevity of the population demands a better understanding of the family factors that influence their integration into society. Therefore, the objective of this research is to analyze how the family influences the social inclusion of older adults in El Arenal parish. To achieve this purpose, the study adopted a qualitative approach and was based on the inductive method, using semi-structured interviews applied to 30 older adults and a social promoter, in order to gather information about their family dynamics and level of inclusion in the community. The findings show that, although the family is a fundamental pillar for the integration of older adults, challenges persist, such as the lack of time of family members, social isolation and economic difficulties that limit their participation in community life. Despite the existence of support programs in the parish, problems of access and mobility restrict their effectiveness. It is concluded that the main problems affecting the well-being of the elderly are related to the lack of close family support, economic restrictions and difficulties in accessing services and recreational activities. The family plays a determining role in social inclusion; however, its effectiveness is based on the communication, participation and support it provides to its older members